(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Coffee is one of the most important agricultural commodities in global market. Therefore, the quality of coffee beans is certainly an important factor which notables in considering taste of coffee, especially on flavor profile. Coffee beans produced by farmers in Indonesia are generally â€œinferior quality of coffeeâ€, as mentioned unsorted or ungraded coffee/kopi asalan with defect score more than 225. It is caused by improper processing that is affecting coffee flavor become stink and fermented. Improvement of post-harvest aspects are needed to upgrade coffee quality. This research examine a processing system using Ohmic-based fermentation technology to produce specialty coffee. This research was conducted by setting the temperature (30, 35 and 40oC) and fermentation time (2, 6, 12, and 18 hours). The results showed that this treatments could gain cupping score anging from 81.81 to 85.25 with an average cupping score of 84.03. In this study, the application of 12 hours fermentation time and 35oC temperature generated the highest cupping score of 85.25. The best coffee flavor by applying 30oC temperature was mouthfeel or body with cupping score of 7.81, whereas flavor, aroma and balance were the best characteristic coffee profile by applying 35oC temperature on the fermentation process. On the other hand, fermentation temperature of 40oC generated high preference score of balance, that was 7.84. In term of fermentation time, the best characteristics of 2 hours and 12 hours fermentation were flavor and aroma, respectively. Enrekang Arabica coffee has 21 flavor profiles. b